Structure and Fragmentation Scale of a Massive Star-forming Filament in NGC 6334: High-resolution Mid-infrared Absorption Imaging with JWST - Philippe André; Michael Mattern; Doris Arzoumanian; Yoshito Shimajiri; Annie Zavagno; Daisei Abe; Delphine Russeil (The Astrophysical Journal Letters)
Dense filaments are believed to be representative of the initial conditions of star formation in molecular clouds. We have used the MIRI instrument on JWST to image the massive filament NGC 6334M at d  ∼ 1.3 kpc with unprecedented resolution and dynamic range at 7.7 and 25.5 μ m. Our observations reveal the fine structure of the filament in absorption against mid-infrared background emission. From the absorption data, we derive high-resolution column density maps and perform a detailed analysis of the structure of NGC 6334M. We find a median filament width of 0.12  ±  0.02 pc at both wavelengths, resolved by almost two orders of magnitude with MIRI, and consistent with the typical half-power width of Herschel filaments in nearby ( d  < 500 pc) clouds. The JWST data also reveal the presence of a quasi-periodic series of side filaments with a similar projected spacing of 0.125  ±  0.015 pc. Combining our JWST results with Spitzer and APEX/Herschel data, we perform a study of cloud structure over four orders of magnitude in linear scale. A convergence test shows that our width estimates for NGC 6334M are robust and reflect the presence of a true characteristic scale. While there is evidence of a Kolmogorov-like spectrum of small-scale fluctuations down to the 1.6 × 10 ^−3 pc resolution of the JWST observations, we identify a break in the power spectrum of column density fluctuations at a scale  ∼0.1–0.4 pc comparable to the width of NGC 6334M and its side filaments. This characteristic scale  ∼0.1 pc has important implications for the origin of the star formation efficiency in dense gas and the initial mass function.